PEMBINAAN KECERDASAN MORAL PELAJAR MELALUI ORGANISASI KEMASYARAKATAN - Ramadhan, Putri Utami (Mozaic : Islam Nusantara, 2021)
The problem of student character or morals is a serious problem for the Indonesian people, the decline in morals and morals that continues to be eroded by the times is one of the impacts of the decline in the character of citizens. The rise of cases of bullying, student brawls, free sex, drugs, motorcycle gangs, to the current Korean wave must be a serious concern and it is necessary to find the best solution to improve the morals and morals of the younger generation. This study aims to obtain information about fostering the moral intelligence of citizens, especially students, carried out by community organizations. The approach used in this research is a qualitative approach with a descriptive method. The results of the study found that the community organization in this case, namely IPPNU had various objectives, one of which was to foster the moral intelligence of its members. The moral intelligence that IPPNU wants to achieve and build is universal values, namely the character values ​​of mabadi khairu ummah (character values ​​of being honest, trustworthy and keeping promises, being fair, mutual cooperation, and consistent) and the character of ahlussunnah wal jamaah (values ​​to behave moderately and fairly, to be balanced between humans, nature, and God, and to be tolerant).